EGR1 is essential for deoxynivalenol-induced G2/M cell cycle arrest in HepG2 cells via the ATF3ΔZip2a/2b-EGR1-p21 pathway. (15th December 2018) - Yuan, Liping; Mu, Peiqiang; Huang, Boyan; Li, Hui; Mu, Haibin; Deng, Yiqun
Highlights: EGR1 is essential for deoxynivalenol-induced G2/M cell cycle arrest. The upregulation of EGR1 is regulated by ATF3ΔZip2a/2b after deoxynivalenol treatment. Expression of ATF3ΔZip2a/2b is mediated by histone H3K9ac and H3K27ac after deoxynivalenol treatment. Abstract: Deoxynivalenol (DON) is a type B trichothecene mycotoxin that exerts multiple toxic effects on plants, animals and humans. Several reports have shown that DON leads to G2/M cell cycle arrest. However, its molecular mechanism is still unclear. In this study, we showed that DON induced strong G2/M cell cycle arrest in HepG2 cells, and the cell cycle-inhibitory protein p21 was highly upregulated by DON. Further analysis showed that the cell cycle regulating gene EGR1 was highly induced by DON and that EGR1 knockdown abolished the upregulation of p21 and G2/M cell cycle arrest. Furthermore, we showed that the induction of EGR1 was regulated by the stress-responsive transcription factor ATF3. ATF3ΔZip2a/2b, which is a DNA binding domain truncated isoform of ATF3, was upregulated by DON. ATF3 knockdown weakened the expression induction of EGR1 and G2/M cell cycle arrest by DON. Moreover, the upregulation of ATF3ΔZip2a/2 highly depended on the enhanced presence of histones H3K9ac and H3K27ac. H3K9ac and H3K27ac were enriched at the promoter region of ATF3 following the DON treatment, and the knocking down of the genes responsible for H3K9ac and H3K27ac abolished the upregulation of ATF3 by DON. In summary, we found that DON induced G2/M cell cycle arrest by sequentially inducing the expression of ATF3ΔZip2a/2b, EGR1 and p21, and EGR1 played an essential role in this process, which is a novel molecular mechanism of cell cycle arrest by DON and is important for understanding its toxicology.